Penerapan Penilaian Otentik Dalam Pembelajaran Pendidikan Agama Islam Di SMP Negeri 6 Payakumbuh - Annisa Ulhusna; Muhiddinur Kamal; Zulfani Sesmiarni; Arifmiboy Arifmiboy (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The background of this research is that the attitude assessment used is only one method, namely by asking students whether they perform the morning prayer. Other methods provided, such as previous exposures, have not had the opportunity to apply them. Then there are difficulties encountered when applying authentic assessments in this aspect of attitude. Based on this, this study aims to look at the implementation that is currently underway at SMP Negeri 6 Payakumbuh, especially the affective aspects and the obstacles faced by teachers when implementing this authentic assessment. The type of research used in this research is descriptive qualitative which is located at SMP Negeri 6 Payakumbuh. Data collection techniques used are interviews, observation and documentation. Data analysis was carried out by means of data reduction, data analysis, and drawing conclusions. The results of the study show that Islamic Religious Education Teachers have implemented authentic assessment. Especially the affective aspects of Islamic Religious Education teachers apply two ways, namely journal assessment and student observation. Basically, in order to be able to assess the perfect authentic assessment of Islamic Religious Education teachers, it is hindered by several factors. The main factor is the limited time to implement it and the large number of students in one class coupled with the creation of a detailed rubric.